Students' Capability In Answering Multiple Choice Question Of Reading Text At Third Grade Of MTs Darul Hijroh Canden, Rejosari, Polokarto - Istanto, Rahmad Fudi; , Dr. Dwi Haryanti, M.Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
The aims of this research are to describe the students' capability in answering multiple choice question of reading text, the problem faced by students in answering multiple choice question of reading text, and the sources of the problem faced by students in answering multiple choice question of reading text at third grade of MTs Darul Hijroh Canden, Rejosari, Polokarto. This research is a descriptive qualitative research. The writer collets the data by observing teaching learning process, conducting the interview,and documenting some important data, and also conducting a text. The data are taken from the result of the test conducted by the students of third grade MTs Darul Hjroh. The methods of collecting data are observation, interview, documentation and test. The techniques of analyzing data are identifying the result of the observation, identifying the information from the interview with the students, English teacher and staff of boarding school, identifying the result of the test, describing the percentage of each items to categorize and to find the levels of students' capability in answering multiple choice question of reading text by using Arikunto Standard in categorizing, and the last is describing the result of the students' test and students' problems in answering multiple choice question of reading text. The result of the research: 1) The students' capability in answering multiple choice question of reading text can be divided into three category level. They are 14 (63,63%) students in poor level, 6 (27,27%) students in fair level, and 2 (9,10%) students in good level. So, it can conclude that the capability of the students to answer the multiple choice question of reading text is low. 2) The most problem faced by the students in answering multiple choice question of reading passage are almost of all types question become the most problem faced by the students. It is because the percentages of those types of questions are less than 60%. 3) The causes of the problems in answering multiple choice question of reading text are the students lack of vocabulary, the teacher do not give the students effective strategies to comprehend the reading passage and to answer the question, and the students less motivation in English.